The effect of Syrian products planning on the purchasing behavior of foreign consumers - a field study in the UAE - خليل سلوايه, نجم الدين; ميا, علي; وحود, نور (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Product planning takes priority when the product is marketed in foreign markets, as the consumer here by naming it a foreign consumer has a different behavior from the local consumer, so the product planning process took priority in that so that the organization could invade foreign markets, spread its products there and meet the needs of consumers there. The research dealt with the concept of product planning, and its relationship to the product life cycle, and components of product planning in addition to the concept of foreign consumer behavior and the impact of Syrian product planning on the purchasing behavior of foreign consumers. And the dependent variable, the questionnaire was relied on and distributed to a sample of consumers in the UAE markets, and the SPSS program was used to analyze data and study hypotheses using appropriate statistical analyzes. The study reached the most important results: There is a strong relationship between the independent variable (product mix) and the dependent variable (foreign consumer behaviour). There is a strong relationship between the independent variable (product quality) and the dependent variable (foreign consumer behaviour). There is a strong relationship between the independent variable (performance quality) and the dependent variable (foreign consumer behaviour). There is a strong relationship between the independent variable (the quality of conformity) and the dependent variable (the behavior of foreign consumers). There is a strong relationship between the independent variable (product design and attributes) and the dependent variable (foreign consumer behaviour). There is a strong relationship between the independent variable (packaging) and the dependent variable (foreign consumer behaviour). There is a strong relationship between the independent variable (explanation) and the dependent variable (foreign consumer behaviour). There is a strong relationship between the independent variable (name and brand) and the dependent variable (foreign consumer behaviour).